Buttering for FSW: Enhancing the fracture toughness of Al-Fe intermetallics through nanocrystallinity and suppressing their growth. (24th March 2023) - Beygi, R.; Carbas, R.J.C.; Barbosa, A.Q.; Marques, E.A.S.; da Silva, L.F.M.
Abstract: The formation of intermetallic compounds (IMCs) is an inevitable phenomenon during friction stir welding (FSW) of dissimilar metals. Majority of approaches that have ever been used to control the IMC thickness during FSW have been process-based. In the present study, the objective was to develop a novel metallurgical approach to control the growth and microstructure of AlFe IMCs during FSW. To do so, the faying surface of a structural carbon steel (CS) was buttered with stainless steel (SS) prior to the FSW process. The joints were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to study the intermetallic compounds. Tensile specimens with holes in the joint area were prepared and tested. The fracture surfaces of the specimens were studied by SEM. The analyses showed that the buttering caused the tensile strength and the fracture elongation to increase by 60 % and 250 %, respectively. SEM and TEM results revealed that there were two mechanisms responsible for this improvement. First, the thinning of the IMC layer and second, the nano-crystallinity of the IMC. The underlying physical phenomenon in controlling the IMCs thickness by this approach is discussed, highlighting the mechanisms by which the mechanical properties are enhanced. The alloying elements Cr and Ni introduced by the buttering technique were found to play the major role in controlling the thickness and nano-crystallinity of the IMC layers in the FSW of Al to St. It was found that the harmful intermetallic compounds in FSW of dissimilar metals can be effectively controlled by the alloying elements imparted through buttering before FSW. Graphical abstract: Unlabelled Image Highlights: Buttering before FSW can improve the joint strength without the need for complex procedural changes. The thickness of the intermetallic layers of the joint can be effectively controlled by buttering. The grain refinement and thinning of the intermetallic layer resulted from buttering increases the toughness.